Mitigasi Penanggulangan Tumpahan Minyak (Oil Spill) di Perairan Laut Kepulauan Riau Berdasarkan Law Of The Sea Convention - Imelia Damai Agusthin; Sasqia Putri Ramadhani; Muhammad Adymas Hikal Fikri (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
In early March 2024, black oil waste was found along the shores of Bintan Island in the Riau Islands Province. This is not the first time an oil spill has been discovered on Bintan Island; such incidents recur annually. This article discusses the legal policies of the applicable maritime law convention related to this case, as well as the environmental restoration mechanisms due to oil spills in marine waters. This research adopts a juridical-normative approach, employing the Statute Approach. Data analysis is conducted qualitatively, using secondary data sources, and employing legal document analysis and literature study methods. UNCLOS provides a strong legal foundation for countries to preserve and protect the marine environment, including actions in response to oil spills. The legal provisions discussed in this article are Article 1 Paragraph (4), Article 192, Article 193, Article 233, Article 220, and Article 230 of UNCLOS 1982, covering definitions, state obligations and autonomy, the role of states, enforcement authority, and compensation obligations. The primary objective in the initial emergency response is to control the movement of the oil as much as possible and minimize its toxic impact on the marine environment. Various methods that can be chosen include in-situ burning, oil dispersants, using absorbents, and bioremediation. After cleaning the oil from the waters, attention shifts to rehabilitating the affected ecosystem, involving restoration steps such as restoring natural habitats and replanting marine vegetation, with collaboration between the government, community, and local entities for positive future impacts.